Toward the software realization of a GSM base station. - Turletti, T.
Advances in processor and analog-to-digital conversion technology have made the software approach an increasingly attractive alternative for implementing radio-based systems. For mobile telephony base stations, the advantages with the new architecture are obvious: great cost savings by using one transceiver per base transceiver station (BTS) instead of one per channel, tremendous flexibility by moving system-specific parameters to the digital part, and allowing the support of a wide range of modulation and coding schemes. This paper considers the software implementation of a GSM BTS, and analyzes the performance of each of its radio interface modules. The performance of each software module is evaluated using both a % CPU metric and a processor-independent metric based on SPEC benchmarks. The results can be used to dimension systems, e,g., to estimate the number of software-based GSM channels that can be supported by a given processor configuration, and to predict the impact of future processor enhancements on BTS capacity. Two novel aspects of this work are the portability of the software modules and the platform-independent evaluation of their computational requirements
Keywords: BTS capacity; CPU metric; GSM base station; SPEC benchmarks; Analog-to-digital conversion technology; Base transceiver station; Channel coding; Coding; Mobile telephony base stations; Modulation; Performance; Processor configuration; Processor technology; Processor-independent metric; Radio interface modules; Radio-based systems; Software complexity; Software environment; Software module library; Software realization; Software-based GSM channels; System-specific parameters